The evolution of the cytoskeleton. - Wickstead, B; Gull, K (2011)
The cytoskeleton is a system of intracellular filaments crucial for cell shape, division, and function in all three domains of life. The simple cytoskeletons of prokaryotes show surprising plasticity in composition, with none of the core filament-forming proteins conserved in all lineages. In contrast, eukaryotic cytoskeletal function has been hugely elaborated by the addition of accessory proteins and extensive gene duplication and specialization. Much of this complexity evolved before the last common ancestor of eukaryotes. The distribution of cytoskeletal filaments puts constraints on the likely prokaryotic line that made this leap of eukaryogenesis.